The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/phar.2219
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cangrelor as a Bridge to Left Ventricular Assist Device Implantation in a Patient with a Recent Drug‐Eluting Stent Who Developed Acute Tirofiban‐Related Thrombocytopenia

Abstract: Current guidelines emphasize the need for at least 6-12 months of oral dual antiplatelet therapy consisting of aspirin and a P2Y12 inhibitor following drug-eluting coronary artery stent implantation. In patients with recently implanted coronary artery stents who require urgent cardiac or noncardiac surgery, the benefits of maintaining oral dual antiplatelet therapy must be carefully weighed against the risks of excessive bleeding, and current practice is largely guided by individual surgeon preferences. When t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…8 Retrospective studies of cangrelor bridging for NCS report either no bleeding or minor procedural bleeding (Table 4), suggesting that this is a safe approach to perioperative platelet inhibition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Retrospective studies of cangrelor bridging for NCS report either no bleeding or minor procedural bleeding (Table 4), suggesting that this is a safe approach to perioperative platelet inhibition. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the BRIDGE trial reported a low incidence of preoperative ischemic events, and retrospective studies of cangrelor bridging for NCS report a low incidence of perioperative MACE (Table 4). 8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Thus, cangrelor bridging appears to be an effective approach for mitigating the risk of perioperative MACE.…”
Section: Table 4 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…22 To date, there is no randomized trial of bridging with cangrelor in NCS, and limited observational experience are available with heterogenous prescribing and monitoring practices, which may contribute to suboptimal outcomes. [10][11][12][13][14][15][16] Likewise, data on bridging use of short-acting GPIs are heterogeneous as well with regard to type of surgery, inclusion criteria, time windows between stent implantation or ACS and surgery, and antiplatelet strategies during the perioperative period which may partly explain the reported variability in success rates. 37 Despite the inclusion of a similar miscellaneous of surgical procedures, we believed that the strength of our study is a standardize case by case approach evaluation to weight the ischemic and bleeding risk and the use of a bridging protocol with a close postoperative monitoring which could have had a positive impact on our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, there is limited reported data on the use of cangrelor among patients undergoing noncardiac surgery (NCS). [10][11][12][13][14][15][16] On this background, we report the results of a prospective, multicenter registry describing realworld experience of a prespecified bridging protocol using cangrelor conducted in patients referred to nondeferrable intermediate to high bleeding risk surgery requiring withdrawal of DAPT.…”
Section: Introductionmentioning
confidence: 99%